Exploring and Reflecting on Problems and Challenges in Teaching Culture for English Young Learners - Talenta, Pratama Irwin; Angie Pavita, Maria Dimitrij; Amrullah, Yozar Firdaus (Universitas PGRI Semarang, 2023)
This study aims to reflect on the problems and challenges in teaching culture to English Young Learners (EYL) primarily related to the English context. The study focused on two objectives; to find out problems and challenges faced by the teacher in teaching culture for EYL, as well as the effective methods used to teach culture for EYL. Recently, many more pre-schools in Indonesia have offered English as a major in the learning process. For example, KB TK Hj Isriati Baiturrahman 2 made English as a central subject in daily life. Ideally, the teachers are required to know English culture besides the teaching itself. However, they found some problems in teaching culture when they asked the students to practice how to say, go to the toilet in English; it made students perspectives in their home opposites. This study tried to investigate this issue from the teachers problems. The interviews and classroom observations data showed that the cultural aspects of language were still not good. The possible strategies also showed a solution to face the problems. Thus, teaching English in Indonesia should consider the culture because to communicate functionally using the language and the students have to be familiar with the culture.